The sustainability energy initiatives in Malaysian universities / Nurul Shafiqqa Bidin - Bidin, Nurul Shafiqqa (Faculty Architecture, Planninng and Surveying, 2015)
Sustainable energy is an energy sources that can help Earth to sustain balanced, give a healthy to ecosystems and the most important is to human life. Sustainable energy is also about the energy that can renewable without give effect to environment. While fossil fuels, coal, oil and gas are not sustainable energy sources because when it bum to create energy, it create massive levels o f greenhouse gases,which result in human impact on the global climate. That impact is creating an imbalance in the Earth’s climate that is already impacting human life. These researches want to investigate the achievability of sustainable energy in Malaysian Universities. The objective o f this research is to identify the initiative o f sustainable energy, to assess the effect o f sustainable energy used and lastly is to make a recommendation to improve awareness about the sustainable energy. To determine the achievability of sustainable energy in Malaysian Universities, the primary data through interview were conducted in three o f Malaysian Universities. Each university represents the two people in interview session. To identify the initiative o f sustainable energy is through the secondary sources. From the findings and discussion shows that achievability in Malaysian Universities in implementation o f sustainable energy has own way. But to implement fully the university have a constraint. For finding and discussion, the most initiative o f sustainable energy in Malaysian Universities is lightemitting diode (LED) lamp. Most a universities applied it. The second higher is an applied sensor technology. For the vision and mission, most of the universities not achieve yet in sustainable energy. Based on the findings and discussion the benefit of implementation o f sustainable energy in universities building is can reduce using electrical energy and can decrease the electrical bill. This shows the implementation o f sustainable energy can give the many benefit to university itself and give good effect to human and environment.